Implikasi Kedudukan KPK Sebagai Rumpun Kekuasaan Eksekutif Berdasarkan Undang-undang Nomor 19 Tahun 2019 - Habibi, Miftakhur Rokhman (Al-Jinayah : Jurnal Hukum Pidana Islam, 2021)
The development of modern state administration constitutes new branches of power outside the Legislative, Executive and Judicial power, as well-known in the concept of “trias politica”. This branch of power is an Independent power with the emergence of a number of independent State commissions. In Indonesia, one such institution is the Corruption Eradication Commission (KPK). However, Law Number 19 of 2019 changed the KPK to become part of the executive power. So that, in this paper will discuss about the position of independent state institutions in a constitutional perspective and the implications of establishing the KPK as an executive body. This research is a normative research with the type of doctrinal research. The approach uses statutory approach and a conceptual approach. The results show that independent power does exist in the modern constitutional perspective. However, the establishment of the KPK as an independent institution in the executive clump has several implications, including the transfer of KPK's responsibility to the President, the executive forming the Supervisory Board which regulates the work procedures of the KPK and the KPK becomes the object of the DPR's inquiry rights.